Current trends and emerging patterns in the application of nanomaterials for ovarian cancer research: a bibliometric analysis - Wang, Wenhui; Wei, Jie; Feng, Dingqing; Ling, Bin (Frontiers in Pharmacology, 2024)
Introduction: Ovarian cancer remains to be a significant cause of global cancer-related mortality. In recent years, there has been a surge of studies in investigating the application of nanomaterials in the diagnosis and treatment of ovarian cancer. This study aims to conduct a comprehensive bibliometric analysis regarding nanomaterial-based researches on ovarian cancer to evaluate the current state and emerging patterns in this field.A thorough literature search on the Web of Science Core Collection database was conducted to identify articles focused on nanomaterial-based ovarian cancer researches. The studies that met the inclusion criteria were selected for further analysis. VOSviewer and CiteSpace were applied for the bibliometric and visual analyses of the selected publications.Results: A total of 2,426 studies were included in this study. The number of annual publications showed a consistent upward trend from 2003 to 2023. Notably, China, the United States, and India have emerged as the leading contributors in this field, accounting for 37.39%, 34.04%, and 5.69% of the publications, respectively. The Chinese Academy of Sciences and Anil K. Sood were identified as the most influential institution and author, respectively. Furthermore, the International Journal of Nanomedicine was the most frequently cited journal.In terms of the research focus, significant attention has been directed towards nanomaterial-related drug delivery, while the exploration of immunogenic cell death and metal-organic frameworks represented recent areas of interest.Through comprehensive analyses, an overview of current research trends and emerging areas of interest regarding the application of nanomaterials in ovarian cancer was illustrated. These findings offered valuable insights into the status and future directions of this dynamic field.